E-SATISFACTION SEBAGAI MEDIASI PENGARUH KUALITAS LAYANAN DAN KUALITAS SISTEM TERHADAP CONTINUANCE INTENTION - Ika Susilowati (Juremi: Jurnal Riset Ekonomi, 2025)
This study employs primary data and is quantitative in nature. Questionnaires and a review of the literature were used to gather data. The purpose of this study is to identify the factors that affect the intention to continue. The subjects in this research are BSI mobile banking users in Purwokerto. In this research, samples taken using a purposive sampling technique are called non-probability sampling. This implies that there is no probability for any individual in the population to be included in the sample. There were 220 responders in the study's samples. This study used the Structural Equation Modeling (SEM) approach, which is characterized as an analysis that blends path analysis, structural models, and factor analysis techniques. Analytical methods are used to interpret and draw conclusions from data sets. Data resulting from the research were processed and analyzed using the SEM (Structural Equation Model) program from the smart PLS version 3 and SPSS for Windows version 23. The results of data analysis can be concluded that service quality and system quality influence e-satisfaction. Continuence intention is influenced by e-satisfaction, system quality, and service quality. Through e-satisfaction, service and system quality significantly and favorably affect the intention to continue.